Investigation of performance and exhaust emissions of a chromium oxide coated diesel engine fueled with dibutyl maleate mixtures by experimental and ANN technique - Sevinc, Huseyin; Hazar, Haney (Elsevier Sci Ltd, 2020)
Oxygenated fuel additives and thermal barrier coating (TBC) applications are noteworthy subjects that may reduce the exhaust emission levels and improve the performance of vehicles. In this study, the exhaust emission and performance characteristics of chromium oxide (Cr2O3) coated single cylinder diesel engine fueled with dibutyl maleate (DBM) blends were investigated. In addition, an artificial neural network (ANN) which had the ability to reduce experimental repeats, cost and time loss was designed and its performance was examined. Piston crown and valves of diesel engine were treated with chromium oxide. Experiments were carried out with DBM3, DBM6, DBM9 blends that contain 3%, 6%, 9% by volume of DBM, respectively. The results indicated that carbon monoxide (CO), hydrocarbon (HC), smoke density, brake specific fuel consumption (BSFC) values reduced in the isolated engine (IE) whereas nitrogen oxide (NOX), exhaust gas temperature (EGT) and engine vibration (EV) values increased compared to standard engine (SE). The addition of DBM reduced CO, HC, smoke density, EGT, and engine vibration whereas NOX and BSFC values increased in both IE and SE. Consequences of ANN revealed that exhaust emission and performance attributes of an engine can be estimated with high accuracy.
Keywords: Thermal barrier coating; Dibutyl maleate; Diesel engine; Performance; Exhaust emissions; Artificial neural network